Reliability of non-invasive imaging methods in the evaluation of pancreatic parenchyma changes in tumors of the pancreaticoduodenal zone - M.M. Veligotskyy; S.E. Arutyunov; I.I. Yakovtsova; I.V. Ivakhno; O.M. Veligotskyi (Gastroenterologìa)
Background. Pancreatoduodenectomy is a radical surgical intervention in case of neoplasms of the pancreatoduodenal zone. Assessment of changes in the pancreatic parenchyma at the preoperative stage will allow appropriate therapeutic and preventive measures to be taken to reduce the frequency of pancreatic fistula. The purpose of the study: to determine the diagnostic significance of non-invasive imaging methods in the assessment of fibrous changes in the pancreatic parenchyma of patients with neoplasms of the pancreatoduodenal zone. Materials and methods. The study included 82 patients who underwent pancreatoduodenectomy for neoplasms of the pancreatoduodenal zone. The age of the patients varied from 34 to 77 years, there were 42 (50.9 %) men and 40 (49.1 %) women. At the preoperative stage, all patients underwent non-invasive imaging using multidetector computed tomography and ultrasound shear wave elastography (SWE). In the postoperative period, histological studies of pancreatic biopsies taken in the isthmus region were performed. Morphological studies were carried out on a Primo Star microscope (Carl Zeiss) using the AxioCam program (ERc 5s). Ki-67, a marker of proliferative activity, was used to conduct immunohistochemical study. The reaction of alpha-smooth muscle actin (α-SMA) was evaluated by a semiquantitative method depending on the intensity of staining. Primary monoclonal antibodies from Dako (Denmark) and Thermo Scientific were used. Results. According to the applied morphological Ammann’s fibrosis score, mild fibrosis was diagnosed in 23 (28.1 %) patients, moderate — in 22 (26.8 %) patients, severe — in 37 (45.1 %). Immunohistochemical study found that without fibrosis and with mild fibrosis, the average Ki-67 was (6.4 ± 2.3), while in moderate fibrosis, it was (16.1 ± 2.5) (p < 0.05 compared to mild fibrosis), with severe fibrosis, the average Ki-67 indicator was (18.3 ± 2.4) (р < 0.05 compared to mild fibrosis). According to the results of the correlation analysis, a strong positive relationship was found between the expression of α-SMA and stromal Ki-67 (r = 0.75, p < 0.001). In patients with mild pancreatic fibrosis in the postoperative period, the native density of the pancreatic parenchyma at the preoperative stage was 1.5 times (p < 0.001) lower than in the group with moderate fibrosis and 1.9 times (p < 0.001) lower compared to patients with pronounced pancreatic fibrosis. According to SWE, the Young’s modulus, which characterizes the stiffness of the pancreatic parenchyma, was highest in severe fibrosis, (8.55 ± 1.75) kPa, which was 2.2 times (p < 0.001) higher than in mild fibrosis and 1.3 times (р < 0.01) higher than in moderate pancreatic fibrosis. According to the results of the correlation analysis, a direct strong relationship was found between the Young’s modulus and the level of stromal Ki-67, α-SMA and the Ammann’s fibrosis score, as well as medium positive correlations of the native pancreatic density with morphological indicators. Conclusions. Non-invasive diagnostic parameters such as parenchymal stiffness according to SWE (sensitivity 90.9 %, specificity 81.2 %) and native density according to computed tomography (sensitivity 69.7 %, specificity 87.5 %) can be used as diagnostic criteria for assessing pancreatic fibrosis in patients with neoplasms of the pancreaticoduodenal zone in the preoperative period.